Polityka gospodarcza w deklaracjach wyborczych kandydatów na Urząd Prezydenta Rzeczypospolitej Polskiej w 2010 roku - KAMOLA-CIEŚLIK, Małgorzata (Przegląd Politologiczny, 2018)
The paper presents the differences and similarities in the economic platforms of candidates for presidency of Poland. An attempt is also made to assess which promises made by the candidates in the realm of economy generated support, and which were responsible for the conflicts arising between them. Economic problems were the subject of the electoral declarations of many candidates. Privatization, the tax system and the development of businesses attracted most attention. The visions of the Polish economy presented by the candidates were similar. Only Janusz Korwin-Mikke advocated a minimum of state intervention in economic life. The commercialization of the national health system and agricultural subsidies were the centre of the disputes between Bronisław Komorowski and Jarosław Kaczyński. The fact that the former won a judicial argument about the privatization of the health system did not help him to win over undecided voters, which was clearly evidenced in the opinion polls conducted before the election. Komorowski was elected Poland’s president by a small majority. Kaczyński’s defeat was due to the fact that he commanded a significant negative electorate.